A Portrait of Pawn Shops Loans as a Survival Strategy During COVID-19 Pandemic - Dewi, Putri Kemala; Ahsan, Abdillah; Rahmayanti, Krisna Puji (UI Scholars Hub, 2025)
This study investigates the impact of the number of financing loans before and after the pandemic and analyzes internal and external factors of PT Pegadaian on Outstanding Loans as the dependent variable by using data from PT Pegadaian during 2018–2020. The statistical method used for this analysis is the Generalized Least Squares (GLS). The result shows that the financing loan by PT Pegadaian has significantly higher during the COVID-19 pandemic, then macroeconomic characteristics, ceteris paribus. In addition, this study found an increase in the need for pawning in society, indicated by the increase in Outstanding Loan (OSL) in PT Pegadaian.